Running speed, energy cost of uphill running and overall energy expenditure during the Etna Marathon race (0 - 3000 m a.s.l.): a case report - Antonutto, G.; Messina, G.; Zadro, I. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Introduction: Etna Marathon is a particular race starting from sea level and reaching, after 43 km, the summit of Mount Etna (Sicily, Italy) at 3000 m above sea level (a.s.l.). The record time during the 2004 edition was 4 h 12 min and 17 s. Because of the fall of the Oxygen partial pressure as a function of altitude, this race represents a peculiar challenge for the aerobic metabolism. Therefore, aims of this study were: i) to evaluate the energy cost of uphill running, ii) to calculate the fraction of VO2max utilised during the race by the athlete running at his endurance speed and iii) to calculate the overall energy expenditure of the race above the resting metabolism. Materials and Methods: This study was performed on one male runner (36 years, stature 1.66 m, body mass 56 kg) whose individual Marathon record, on flat terrain, was 2 h 23 min. This athlete won the 2004 and the present (2005) edition of the Etna Marathon. His VO2max was determined during two laboratory sessions separated by 5 days. During the first session, the experimental protocol consisted of four steps of 5 min running on a treadmill at 15, 17, 18 and 19 km/h. The steps were separated by 6 min of recovery. During the last minute of each step, the air expired by the athlete was collected into Douglas bags and the expired O2 and CO2 fractions were determined together with pulmonary ventilation (VE). This data allowed us to calculate O2 consumption (VO2), CO2 production (VCO2) and respiratory ratio (RER). Heart rate (HR) was also recorded continuously during the test. The second session was dedicated to the assessment of VO2max. The experimental protocol consisted of two steps of 10 min each. The first step was run at 13 km/h with the treadmill inclined at 3% for 5 min and at 9% for the remaining 5 min. During the second step, run at the same speed, the treadmill was inclined at 6% (5 min) and at 12% (5 min). Between the steps the subject rested for 6 min. Also in this case VO2, VCO2, VE, RER and HR were determined as described above. These data allowed us to calculate VO2max, the relationship HR vs. VO2 and the energy cost of running (Cr, J /(kg*m), as obtained from the ratio of VO2 above resting to speed. The Etna Marathon was run 5 days after the last laboratory experimental session. During the race, HR, altitude and running speed were recorded every kilometer. The average incline of the race was 7%. Results and discussion: VO2max above resting amounted to 3.73 LO2 / min (66.6 mLO2 / (min*kg). To take into account the decrease of VO2max as a function of altitude we calculated its weighted average (VO2max-alt) over the entire race using altitude and time as weighting factors (VO2max-alt = 63.4 mLO2 / (min*kg)). VO2 during the race was estimated from the actual HR data (recorded during each kilometer) and the HR vs. VO2 relationship previously obtained in the laboratory. Consequently, we estimated the energy cost of running over each kilometer as a function of the incline (Cr, J /(kg*m)). The average Cr amounted to 0,266 mLO2 / (kg*m) corresponding to 5,56 J / (kg*m) a value was close to that determined in the laboratory for the same average incline, i.e. 5.05 J / (kg*min). The subject ran the race in 4 h 5 min and 40 s (new record) the corresponding average speed (vend) amounting to 175.5 m/min (10.53 km/h). Therefrom, we calculated the actual fraction of VO2max, corrected for the altitude, which the subject maintained throughout the race: Fact = Cr * vend / VO2max-alt = 0.266 *175.5 / 63.4 = 0.736 (di Prampero, 1985). According to Saltin (1973) the maximal fraction of VO2max a given subject can maintain is a function of the performance time, as described by: Ftheor = (940 - trun) / 1000. Inserting into this equation the actual performance time of our subject (in minutes) yields Ftheor = 0.695, a value not very far from that calculated above. The overall energy expenditure of the race (Erun) was also obtained from the actual energy cost of uphill running Cr (5,56 J /(kg*m)), the length of the race, and the body mass of the athlete: Erun = Cr * 43000 * 56 = 13388 kJ corresponding to 3195 kcal above the resting metabolism. This same athlete recently (25.9.05) covered the 21.97 km of the "Maratonina di Udine" (essentially at sea level and on flat terrain) in 1h 11 min and 22 s. We therefore estimated the average fraction of VO2max actually maintained throughout the race (from his know VO2max and Cr on flat terrain, according to di Prampero (1985) and from Saltin's equation. The two values turn out to be essentially equal (86% and 86.8%). It is concluded that a) the average speed maintained during long distance running is appropriately described by vend = F VO2max/Cr and b) the equation derived from Saltin's data (1973) yields accurate estimates of the actual fraction of VO2max maintained throughout the race.